Magical Powers of Garbage: An Art and Recycling Experience in Early Childhood Education - Jara Aguirre, Paulina (2024)
This proposal seeks to highlight the expressive possibilities of waste materials in the context of an art workshop with a therapeutic focus. These materials offer communicative possibilities that value different forms of expression while facilitating symbolic play in specific contexts. The experience occurred over a year with children aged 4 to 6 in a nursery school in Viña del Mar, Chile. It focused on two objectives: encouraging creative exploration and the expressive possibilities of working with waste materials, allowing emotional exploration with the material and among participants, and fostering openness to the emotional world and peer interaction. A methodology based on exploration and play was chosen, with structured individual and group work sessions, established guidelines and themes related to the prescribed curriculum for the level. The results make it possible to highlight the benefits of this type of therapeutic intervention in children by strengthening emotional and creative development in the educational context. Likewise, it is noteworthy that the entire educational community is involved in the culture of recycling and reuse.